دور كفاءة المدرب في نجاح عملية الإنتقاء لدى فئة 15 سنة في كرة اليد - مصطفى الطبيب/عيبوط محمد امين (Institut d’Éducation Physique et Sportive / UNIVERSITY OF MOSTAGANEM, 2025)
عنوان الدراسة:دور كفاءة المدرب في نجاح عملية الإنتقاء لدى فئة 15 سنة في كرة اليد . تهدف الدراسة إلى : تحديد مراحل وخطوات الإنتقاء ومميزات اللاعب ،معرفة قدرات وخبرة المدرب المعني بعملية الإنتقاء ، إبرازعلاقة المدرب وأهميته بعملية الإنتقاء ،بيان أهمية الاختبارات عند المدربين لعملية الإنتقاء ، إظهار قواعد التي تنبغي لعملية الإنتقاء والإقتداء بها والوصول بالفئة إلى المستويات المختصة ، كشف كفاءة ودور المدرب لعملية الإنتقاء. الفرض من الدراسة :المدرب وكفاءته له دور إيجابي في عملية الإنتقاء لفئة 15 سنة في كرة اليد . أما الجزئية :كفاءة ومستوى المدرب تلعب دورا في إختيار اللاعبين الموهوبين في كرة اليد ، الاختبارات النفسية والبدنية تلعب دورا هاما في عملية الإنتقاء ،كفاءة المدرب تساهم بشكل كبير في كشف المواهب . العينة :إخترنا العينة العشوائية كونها من أبسط طرق إختيار العينات ،وتمثلت في عشرين مدربا لكرة اليد لفئة الأواسط صنف 15 سنة . الأداة المستخدمة :تم إتباع تقنية الإستبيان الذي يعتبر من أنجح الطرق للحصول عل المعلومات حول الموضوع . النتائج المتوصل إليها :أثبتت الدراسة أن المدرب له دور فعال في عملية الإنتقاء ، وكذلك خبرة المدرب لها تأثير إيجابي على عملية الإنتقاء حيث كلما كان للمدرب خبرة وكفاءة عالية إستطاع التحكم في عملية الإنتقاء . الاقتراحات :إتباع طرق علمية في عملية الإنتقاء _برمجة مخطط خاص بعملية الإنتقاء من حيث الخطوات المنهجية وطرق إستعمال الإختبارات وذالك من أجل التحكم في هذه العملية من حيث الزمن والكيفية من طرف المسؤولين عن هذه الرياضة _ الإهتمام بفئة 15 سنة حيث تعتبر هذه المرحلة من أهم المراحل في عملية الإنتقاء . // // // // // // // Studytitle :the role of coach competence in the successof the selection process for the 15 category in Handball. Study objectives : To define the stages and steps of the selection process and the characteristicsof the player. To understand the abilitiesand experience of the coach involve d in the selection process. To clarify the importance of tests used by coaches during selection. To demonsrate the principles and rules that should guide the selection process and help reach specialized performancelevels. To reveal the competence and role of the coach in the selection process. Purpose of the study : The coach and their competence play a positive role in the selection process for the 15 category in Handball. Hypotheses : The coach ;s competence and level play a significant role in selecting talented handball players . Psychological and physical tests play an important role in selection process . The coach ;s competence significantly contributes to talent identification. Sample : A random sample was chosenas it is one of the simplest sampling methods.The study included 20 handball coaches for the middle youth category 15. Tool used : The questionnaire techninique was used ,as it is one of the most effective methods for gathering information on the subject. Findings : The study demonstrated that the coach plays an essential role in the selection process. Additionally ,the coach ;s experience has a positive impact on selection ;the more effectively they can manage the selectio process. Rcommendation : Adopt scientific methods in the selection process. Devoolop aspecific plan for the selection process ,including methodological steps and use of tests ,to ensure better time and quality management by sports authorities. Pay specal attention to the 15 category ,as it is one of the most crucial in the selection process.
LES-2025-16
Keywords: كفاءة المدرب; عملية الإنتقاء; فئة 15 سنة في كرة اليد; Sport coach; Selection; Handball; U15 CATEGORY